Transformative Learning: The Trojan Horse of Globalization? - Elizabeth A. Lange (Adult Education Research Conference, 2007)
C.A. Bowers suggests that transformative learning ala Paulo Freire may be the Trojan horse of neoliberal globalization by deepening the ecological crisis and colonizing indigenous cultures. This paper critiques Bowers’ argument and proposes a contextual pedagogy for sustainability education.